PERKEMBANGAN WISATA PANTAI SORAKE DITINJAU DARI PENDAPATAN ASLI DESA (PADes) DAN PERUBAHAN SOSIAL - Siwanahono, Tuti Nisra Idayanti; Rinayuhani, Triratna; Santosa (PAWITRA KOMUNIKA : Jurnal Komunikasi dan Sosial Humaniora, 2021)
In the development of the Sorake Beach tourist area, the government has a very important role in preparing, preparing and formulatingstrategies in developing the tourist area, so that development can be well organized and on target according to the need to solve problems in development. The development of sorake beach tourism originated from the working visit of Mr. Jokowi and the team in Nias in 2016. Since then, Sorake beach has received support and attention from the government to develop it. With the formulation of the problem of how the development of the Sorake beach tourism area in terms of the village's original income and social changes. This study aims to see how the development of the Sorake beach tourism area in terms of the village's original income and social changes. The theory used is the theory of the concept of social change from Neil Smleser which consists of 4 indicators, namely: Structural change, change change, mobilization, implementation of control.The research method used in this study is a qualitative descriptive method that describes the actual phenomenon of events in the field.The data technique uses interviews, observations and documents related to research. The results of the study show that the development of Sorake beach tourism has developed very rapidly,the village's original income has increased every year from 2017-2019.And the social changes that have occurred on this Sorake beach tour in Nias culture which have long been embraced are due to the entry of foreig cultures which are contrary to the culture in the area itself.